2005
DOI: 10.1007/s11173-005-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Pd β-Diketonate Complexes with Triethylaluminium

Abstract: Reactions of Pd ( Acac ) 2 and Pd ( Acac ) 2 PPh 3 complexes with triethylaluminium in an inert atmosphere are studied by the NMR and IR, electronic microscopy, and X-ray powder diffraction methods. The final products of conversion of the initial Pd(II) complexes are the Pd(0) nanoparticles with the predominant diameter 2-4 nm. The main factors determining the size of Pd(0) particles and the nature of the ligand shell are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…When passing from DEAC to EASC, the average particle size increases by almost two times. Apparently, nickel-containing nanoparticles act as carriers or substrates for catalytically active centers containing Ni(II)-H or Ni(II)-C fragments, which were previously recorded by 1 H NMR spectroscopy [13,36].…”
Section: Physico-chemical Aspects Of the Formation And Nature Of The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…When passing from DEAC to EASC, the average particle size increases by almost two times. Apparently, nickel-containing nanoparticles act as carriers or substrates for catalytically active centers containing Ni(II)-H or Ni(II)-C fragments, which were previously recorded by 1 H NMR spectroscopy [13,36].…”
Section: Physico-chemical Aspects Of the Formation And Nature Of The ...mentioning
confidence: 99%
“…Since 2004 we have been engaged in detailed investigations of the processes occurring during the formation and functioning of Ziegler hydrogenation catalytic systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Using M(acac) 2 -Red (where M = Co, Ni; Red = AlEt 3 , LiAlH 4 , AlEt 2 (OEt), LiAlH(tert-BuO) 3 ) it was shown that the interaction of acetylacetonate complexes of cobalt, nickel, or palladium with AlEt 3 or LiAlH 4 produced nanoparticles consisting of a metal core (0.7-5 nm) stabilized by a ligand shell.…”
Section: Introductionmentioning
confidence: 99%